The experience of Macedonian foreign language teachers with gifted students - Silvana Neshkovska, Lela Ivanovska, Milena Kasaposka-Chadlovska (Педагошки факултет-Битола, 2020)
Giftedness in the context of foreign language learning still has a status of an underexplored issue which needs special deliberation and thorough studying. The paper at hand investigates the experience of Macedonian foreign language teachers with gifted students. The research is based on a tailor–made questionnaire, in which primary and secondary school teachers of foreign languages (English, German, and French) from a number of Macedonian schools, first, state their viewpoints regarding how they identify gifted students; what their perception of the overall attitude of gifted students is; what difficulties they encounter in teaching gifted students, etc. The questionnaire is also intended to elicit more specific information related to the process of teaching gifted students. More precisely, it looks into the methods, strategies and techniques that foreign language teachers employ in teaching gifted students. Overall, this research shows that Macedonian education has a long way to go in order to master a proper stratagem for dealing with gifted students efficiently in the context of foreign language learning. However, it is also evident that foreign language teachers are aware of that the fact that proper cultivating and harnessing of gifted students’ intellectual potential is an absolute imperative and should be placed high on the list of national priorities.
Keywords: gifted students, foreign language teaching, Macedonian primary and secondary education